GRADE: an emerging consensus on rating quality of evidence and strength of recommendations - Guyatt, Gordon H (BMJ Publishing Group Ltd., 2008)
Guidelines are inconsistent in how they rate the quality of evidence and the strength of recommendations. This article explores the advantages of the GRADE system, which is increasingly being adopted by organisations worldwide